Qualitative questionnaire on the psychosocial wellbeing of mothers of children with BEEC. - Di Grazia, Massimo; Pellizzoni, Sandra; Tonegatti, Luca Giacomo; Rigamonti, Waifro (J Pediatr Urol, 2017)
INTRODUCTION: The bladder exstrophy-epispadias complex (BEEC) represents a spectrum of malformations that affect the anatomical and functional structure of the urogenital system. The parents of patients affected by this condition are subject to particularly stressful situations, such as worrying about their child's health, long hospital stays, concerns about the health and constant need for personal care for their children, that can profoundly compromise the quality of family life. OBJECTIVE: The objective of this explorative qualitative study is to evaluate the social situation and the psychological strategies implemented by the mothers of children between 6 and 10 years of age who are affected by BEEC. STUDY DESIGN: Fourteen mothers of children aged 6-10 years and affected by BEEC (9 boys and 5 girls) were interviewed. Data on the mothers' experiences were collected through semi-structured interviews (Table). RESULTS: The qualitative analysis of the interviews showed that participants described experiences that were characterised by emotions such as fear and anger. Each mother had implemented a different and, sometimes, dysfunctional strategy in order to cope with the complex situation of the son/daughter. The aspects that most clearly emerged from mothers' descriptions were (1) the traumatic situation at the birth of the baby, (2) the sense of embarrassment concerning the pathological condition as the child was growing and the consequent sense of isolation of the mother, and (3) the fluctuation of feelings towards the multidisciplinary staff, which was sometimes seen as an important source of help and some other times as too destabilising and not helpful at all. DISCUSSION: The study provided some insight into the psychological and social conditions experienced by mothers of children with BEEC, which could serve as a basis for developing multidisciplinary teams with greater awareness about families living with this condition and better timing in addressing their needs. CONCLUSIONS: Mothers of children with BEEC show emotional and social difficulties. This is a crucial aspect to consider when planning a multidisciplinary approach to the treatment/therapy, especially considering that children examined in this study are approaching adolescence.
Keywords: Adaptation, Psychological; Adolescent; Bladder Exstrophy; Child; Epispadias; Female; Humans; Long-Term Care; Male; Mother-Child Relations; Mothers; Qualitative Research; Quality of Life; Stress, Psychological; Surveys and Questionnaires; Treatment Outcome